Inequalities changes in health services utilization among middle-aged and older adult disabled people in China: based on CHARLS 2011–2018 - Jin, Shengxuan; Fa, Ruobing; Wu, Jiaqi; Lin, Jiawei; Zhang, Shuyuan; Ali, Majid; Chen, Shaofan; Qian, Dongfu (Frontiers in Public Health, 2024)
Background Multiple intersections, including socioeconomic inequalities, influence health equity for disabled people and sub-populations. However, this association has not been sufficiently analyzed among Chinese-impaired persons. This study aimed to investigate the health services utilization and inequalities in middle and older adult persons with disabilities and subgroups. Methods The China Health and Retirement Longitudinal Study (CHARLS) database in 2011, 2013, 2015, and 2018 were used. Health services utilization was measured by outpatient, inpatient, and self-treatment service utilization. Types of disabilities were classified into six categories. The pooled cross-section regression, concentration index, horizontal inequity index, and concentration index decomposition were used to evaluate inequalities and explore their main contributing factor. Results The utilization and non-utilization of healthcare services showed variations across years (p < 0.05). The CIs and HIs for inpatient health service utilization were positive for all years and disability types. The total CIs of inpatient utilization were the highest (0.248). The highest disparities in utilization of inpatient services were for physical disabilities (0.4515 for CI in 2011), and the highest in self-treatment services were for intellectual disability (0.1538 for CI in 2011). The expenditure factor was the main contributor to inequalities. Chronic disease, educational level, and health insurance factors also contribute to the utilization inequalities. Conclusion Policies should promote medical insurance and assistance for disabled people with serious impairment and poor. It is crucial to improve the provision of basic medical services, including meeting the demand for varied disabilities and the accessibility of facilities and equipment to enhance the access and well-being of people with disabilities.